Mental Health of Health Workers During the COVID-19 Pandemic - Lusiana Ambarsari; Dwi Ernawati (Journal of Midwifery, 2021)
Every day medical health workers have to face a high risk of being infected with COVID-19 and long work shifts. This can cause psychological problems for health workers because the level of anxiety and intolerance of uncertainty increases during the pandemic. This study aims to determine the mental health of health workers during COVID-19. The method used was a scoping review which was carried out by identifying and developing the focus of the review, identifying relevant studies, mapping data with PRISMA Flowcharts, compiling data extraction, making summaries, and reporting the results and discussions that have been made. Based on the results of the search and screening conducted, there were 12 relevant articles. The identification results showed 3 themes, namely mental health disorders of health workers, factors that affectted the mental health of health workers, and coping strategies carried out by health workers in dealing with COVID-19. The conclusion is that mental health disorders experienced by health workers during the COVID-19 pandemic were Posttraumatic Stress Disorder (PTSD), anxiety (anxiety), depression, insomnia, burnout (fatigue), and stress so that health workers need coping strategies in dealing with these situations.